Managing Male Ageing. - Kit, Ng Kok (Marshall Cavendish International (Asia) Ptd Ltd., 2009)
Men are living longer today but many find that they do not have the energy or capability to enjoy this extra bit of life. Advancing age does not mean having to slow down because one is older. With knowledge, awareness and better care of his body, a man can extend his physical, mental and sexual capability and have so many more fulfilling and active years. Men and Health: Getting More Out of Life is about healthy aging in men; it is not a book about diseases. It examines the problems that affect a man's quality of life and how to deal with them. Covering general aspects of aging and andropause,